Das schwindende Vertrauen in die Marktwirtschaft und die Folgen für das Recht - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2009)
– The Eroding Trust in Capitalism and its Consequences for Law: On both sides of the Atlantic, legislators consider a cap on manager income. As a redistributive intervention, the cap would be misplaced. It affects such a small number of persons that the effect on the Gini coefficient would be negligible. Redistribution is, however, not the raison d'être of the rule. The public perceives a very high yearly income of some as a signal for a lack of solidarity in society, especially if recipients are responsible for low wages or even unemployment of many. Based on demoscopic data from Germany, this article shows that generalised trust in capitalism has indeed severely suffered. It explains why this is troublesome news for the legal order. From this starting point, it discusses the justification of a cap on manager income, despite the fact that the German constitution (unlike the US Lochner jurisprudence) in principle protects economic freedom of managers, firms and stockowners. While it cannot offer a strict proof that manager income works as a signal, if offers a piece of indirect evidence. By way of regression analysis, it shows that the Gini coefficient explains interviewees' assessment of the justice of capitalism very well, once one controls for the unemployment rate in the year in question, plus the interaction between both explanatory variables.
Keywords: G34; J31; K22; L22; P10; 330; cap on manager income; generalised trust in capitalism; Gini coefficient; limits to interventions into fundamental freedoms; unemployment rate